Freelance fighters and 'do-it-yourself' terrorism : what lies ahead for Indonesia - Sulastri Osman (2012)
The acts of terrorism perpetrated by Indonesia’s violent fringe in 2011 suggest that organised groups, even ideology, are increasingly irrelevant. Freelance fighters and individual ‘do-it-yourself’ attacks are expected to become more common features of terrorism in the country.